Preparation method of hydrophobic modified material for removing peculiar smell gas
By preparing four -iron/ultra -hydrophobic carbon paper composite material, the problem of low efficiency of odor gas removal of odor gas in existing technology has been solved, and the efficient removal and deep mineralization of enabled soluble odor gas is realized.
Patent Information
- Application Number
- CN202411306044.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-28
AI Technical Summary
When removing odor gases, especially insoluble odor gases, there are problems such as low gas-liquid mass transfer efficiency, high energy consumption, difficult to recover dispersed phase particles, and complex and costly preparation process of composite materials, which is difficult to meet industrial production and Requirements for efficient removal and deep mineralization in daily life.
The nano -grade tetraxide particles are prepared through the water thermal system, and it is scattered in the ethanol solution. The electrostatic is sprayed on the porous carbon paper. After drying and sintering, the four -iron/porous carbon paper composite material is formed. Then, the surface modification and spray polytetrafluoroethylene are then formed to form a composite material for tetraxidine -dioxide/ultra -hydrophobic carbon paper.
This method improves the affinity of catalysts to enabled soluble odor gas, promotes the rapid transmission of gas to catalytic activity sites, and significantly improves the efficiency of the fenton system for the removal of enabled odor gas gas.
Smart Images

Figure CN119368177A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental governance, and in particular relates to a method for preparing a hydrophobic modified material for removing odorous gases. Background Art
[0002] Odor gas pollutants are extremely harmful to human health and the environment. For human health, odorous gases not only irritate human organs and cause damage, but also have a certain risk of cancer; for the environment, odorous gases also form aerosols, photochemical smog, greenhouse gases and other harmful substances. Therefore, how to effectively remove odorous gases has attracted widespread attention.
[0003] Heterogeneous Fenton oxidation is one of the more efficient methods for removing odorous gases. Improving the catalytic material to improve the catalytic oxidation capacity of the Fenton system is a widely used method to improve the degradation efficiency of odorous gases. When heterogeneous Fenton removes odorous gases, its removal efficiency is not only affected by the catalytic degradation efficiency, but also by the fact that odorous gas molecules need to diffuse to the surface of the solid catalyst through gas-liquid mass transfer to react with hydroxyl radicals. In practical applications, the rate of the gas-liquid mass transfer process is also the key to the efficient degradation and deep mineralization of odorous gases by the heterogeneous Fenton system.
[0004] Improving the mechanical stirring efficiency, adding dispersed phase particles or compounding catalytic materials with dispersed phase particles are effective methods to improve the gas-liquid mass transfer efficiency of odorous gases. However, for odorous gases with extremely low solubility in water, the above methods have limited effect on promoting their gas-liquid mass transfer efficiency, and there are problems such as increased energy consumption, difficulty in recycling dispersed phase particles, which can easily cause secondary pollution, and complex and costly preparation of composite materials. They cannot meet the requirements of industrial production and daily life for efficient removal and deep mineralization of odorous gases. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a hydrophobic modified material for removing odorous gases in view of the above shortcomings of the prior art. The composite material prepared by the method has a stable structure and can be applied to the Fenton system to efficiently remove odorous gases, especially to improve the degradation rate of poorly soluble odorous gases.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a hydrophobic modified material for removing odorous gases comprises the following steps:
[0008] a) Preparation of nanometer-sized Fe3O4 particles by hydrothermal method;
[0009] b) dispersing the nano-iron tetroxide particles in an ethanol solution, electrostatically spraying the nano-iron tetroxide particles on one side of the surface-treated porous carbon paper, and drying and sintering the nano-iron tetroxide particles to obtain an iron tetroxide / porous carbon paper composite material;
[0010] c) immersing the ferroferric oxide / porous carbon paper composite material in an ammonium sulfide solution, washing and drying, to obtain a surface-modified ferroferric oxide / porous carbon paper composite material;
[0011] d) preparing a polytetrafluoroethylene (PTFE) spray liquid, and electrostatically spraying it on the other side of the porous carbon paper, i.e., the side not coated with ferroferric oxide particles, and obtaining a ferroferric oxide / super-hydrophobic carbon paper composite material after high-temperature sintering.
[0012] Preferably, in step a), the diameter of the ferrosoferric oxide particles is 80-200 nm.
[0013] Preferably, in step b), the surface treatment of the porous carbon paper includes: soaking the porous carbon paper in urea solution, deionized water, sodium hydroxide solution, anhydrous ethanol and deionized water in sequence for surface modification, the concentration of the urea solution is 4.0-6.0 mol / L, the concentration of the sodium hydroxide solution is 0.8-1.2 mol / L, and the soaking time is 15-20 min; then, ultrasonication and drying steps are performed to obtain the surface-treated porous carbon paper. Surface treatment helps to form abundant functional groups on the surface of the carbon paper, thereby constructing a stable and efficient composite material.
[0014] Preferably, in step b), each 1g of nano-iron tetroxide particles is dispersed in 8-15mL of anhydrous ethanol; the positive electrode voltage used for electrostatic spraying is 8.0-13.0 kV, the negative electrode voltage is 2.0-3.0 kV, the injection speed is 0.25-0.40 mm / min, and the syringe translation speed is 100-300 mm / min; the sintering temperature is 310-380°C, and the sintering time is 0.4-1.2 hours. By spraying the iron tetroxide particles on the surface of the porous carbon paper, the hydrophilicity of the composite material can be improved, and the catalytic efficiency can be further improved. Sintering is to improve the interlayer adhesion, that is, the stability of the adhesion of the iron tetroxide particles. If the sintering temperature is too low, the adhesion of the iron tetroxide particles to the surface of the carbon paper is insufficient; if the sintering temperature is too high, it will affect the morphology of the iron tetroxide surface.
[0015] Preferably, in step c), the concentration of the ammonium sulfide solution is 0.2-0.4 mol / L, the reaction temperature is 45-55°C, and the reaction time is 10 min. The addition of ammonium sulfide can form Fe-S reaction active sites on the surface of the ferroferric oxide particles, further improving the catalytic oxidation performance of the ferroferric oxide surface.
[0016] Preferably, in step d), the mass fraction of polytetrafluoroethylene in the polytetrafluoroethylene spraying liquid is 52%-65%, the solvent is water, and ultrasonic dispersion and magnetic stirring are required before spraying; the positive electrode voltage used for electrostatic spraying is 19.0-23.0 kV, the negative electrode voltage is 1.5-3.0 kV, the injection speed is 0.25-0.40 mm / min, and the syringe translation speed is 100-300 mm / min; the sintering temperature is 310-360°C, and the sintering time is 0.3-0.8 hours. The role of spraying PTFE is to construct a hydrophobic layer, which helps the adsorption of hydrophobic gases. Sintering can further improve the interlayer adhesion.
[0017] Another object of the present invention is to provide a ferroferric oxide / super-hydrophobic carbon paper composite material prepared by the above method.
[0018] The present invention has the following beneficial effects:
[0019] The present invention provides a method for preparing a hydrophobic modified material for removing odorous gases, wherein the preparation method obtains a ferroferric oxide / super-hydrophobic carbon paper composite material by modifying both sides of a porous carbon paper. By attaching ferroferric oxide particles to the surface of the carbon paper and spraying a PTFE solution, the affinity of the catalyst for sparingly soluble odorous gases can be effectively improved, so that the sparingly soluble gases are quickly transmitted to the catalytic active sites, thereby greatly improving the removal efficiency of the Fenton system for sparingly soluble odorous gases. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 Schematic diagram of the preparation process of hydrophobic modified materials;
[0022] In the figure: (1) is nanometer-scale ferroferric oxide particles, (2) is surface-treated porous carbon paper, (3) is ferroferric oxide / porous carbon paper composite material, (4) is surface-modified ferroferric oxide / porous carbon paper composite material, and (5) is ferroferric oxide / superhydrophobic carbon paper composite material.
[0023] Figure 2 This is a SEM image of the nano-sized ferrosoferric oxide particles in Example 1;
[0024] Figure 3 This is the hydrophobic surface of the ferroferric oxide / super-hydrophobic carbon paper composite material in Example 1. DETAILED DESCRIPTION
[0025] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0026] Example 1
[0027] Preparation method of hydrophobic modified material Figure 1 As shown, the method comprises preparing nano-sized ferroferric oxide particles (1), surface treating porous carbon paper (2), preparing ferroferric oxide / porous carbon paper composite materials (3); preparing surface-modified ferroferric oxide / porous carbon paper composite materials (4), and preparing ferroferric oxide / super-hydrophobic carbon paper composite materials (5). Specifically, the method comprises the following steps:
[0028] Weigh 0.95 g of anhydrous FeCl3, 2.40 g of anhydrous sodium acetate and 0.68 g of sodium citrate into a beaker, add 60 mL of ethylene glycol, ultrasonically shake and mechanically stir until the solution is orange-yellow and transparent, then pour into the reactor and react at 200 °C for 10 h. The product is washed with anhydrous ethanol, deionized water and ultrapure water respectively and freeze-dried for 24 h to obtain Fe3O4 particles. Figure 2 is the SEM image of the Fe3O4 particle, and its diameter is about 140 nm.
[0029] The porous carbon paper was surface modified by soaking in urea solution, deionized water, sodium hydroxide solution, anhydrous ethanol and deionized water successively, wherein the concentration of the urea solution was 4.5 mol / L, the concentration of the sodium hydroxide solution was 1.0 mol / L, and the soaking time was 16 min; then, the surface-treated porous carbon paper was obtained by ultrasonic and drying steps.
[0030] 1.0 g of the above-mentioned ferroferric oxide particles were weighed and dispersed in 10 mL of anhydrous ethanol. The above-mentioned ferroferric oxide suspension was sprayed on one side of the carbon paper by electrostatic spraying. The electrostatic spraying experimental conditions were: positive voltage of 10.0 kV, negative voltage of 2.5 kV, injection speed of 0.35 mm / min, and syringe translation speed of 200 mm / min. The above-mentioned electrostatically sprayed sample was placed in a tubular furnace and sintered at 350°C under nitrogen atmosphere for 0.5 h to obtain a Fe3O4 / carbon paper composite material, in which the mass fraction of Fe3O4 was about 20%.
[0031] The ferroferric oxide / porous carbon paper composite material was immersed in a 0.25 mol / L ammonium sulfide solution at a reaction temperature of 50°C for a reaction time of 10 min. After washing and drying, a surface-modified ferroferric oxide / porous carbon paper composite material was obtained.
[0032] Electrostatic spraying was used to spray a 60% tetrafluoroethylene spray liquid (the solvent was water) on the other side of the carbon paper. The specific experimental conditions for electrostatic spraying of tetrafluoroethylene were: positive voltage of 22.0 kV, negative voltage of 2.5 kV, injection speed of 0.30 mm / min, and translation speed of 200 mm / min. The above sample was placed in a tubular furnace, heated to 350°C at a heating rate of 5°C / min and maintained for 30 minutes to prepare a Fe3O4 / super-hydrophobic carbon paper composite material. The hydrophobic surface morphology of the ferroferric oxide / super-hydrophobic carbon paper composite material is shown in FIG. Figure 3 As shown, linear polytetrafluoroethylene is evenly distributed on the surface of carbon paper.
[0033] A Fenton system was constructed using a circulating bubbling reaction device to degrade n-octane. The bubbling reaction device consists of a high-purity air cylinder, a mass flowmeter, an n-octane emission chamber, and a bubbling glass column. The inner diameter of the bubbling glass column is 8 cm and the height is 35 cm. The experimental solution volume during the reaction is 1 L. The gas flow rate is 50 mL / min, and the n-octane concentration is about 0.8 g / m 3 , the system pH = 4. 2.5g of Fe3O4 / carbon paper superhydrophobic composite material was added, and the concentration of odorous gas at the inlet and outlet was detected by gas chromatography-hydrogen flame ionization detector to calculate the degradation rate. The experimental results showed that under the above conditions, the removal rate of n-octane was 89.8%. The composite material combines efficient catalysis and mass transfer to construct a catalytic oxidation-mass transfer interface.
[0034] Comparative Example 1
[0035] Fe3O4 particles were prepared by the method described in Example 1, and 0.5 g of Fe3O4 particles were added to carry out the degradation experiment of n-octane in the Fenton system under the same implementation conditions as Example 1. The experimental results show that under the above conditions, the n-octane removal rate is only 22.3%.
[0036] Comparative Example 2
[0037] Fe3O4 particles were prepared by the method described in Example 1. Under the same conditions as in Example 1, 0.5 g of Fe3O4 particles and 2.0 g of carbon paper were added to carry out the degradation experiment of n-octane in the Fenton system. The experimental results showed that under the above conditions, the n-octane removal rate was 57.5%.
[0038] Comparative Example 3
[0039] The surface modified ferroferric oxide / porous carbon paper composite material was prepared by the method described in Example 1. Under the same conditions as in Example 1, 2.5 g of the surface modified ferroferric oxide / porous carbon paper composite material was added to carry out the degradation experiment of n-octane in the Fenton system. The experimental results show that under the above conditions, the n-octane removal rate is 63.5%.
[0040] Comparative Examples 1-3 show that single ferroferric oxide particles, ferroferric oxide particles attached only to the surface of carbon paper, and ferroferric oxide / porous carbon paper composite materials without PTFE hydrophobic treatment, all fail to achieve good degradation effects. This is because the composite material of the present invention combines efficient catalysis and mass transfer to construct a catalytic oxidation-mass transfer interface.
[0041] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a hydrophobic modified material for removing odorous gases, characterized in that: The following steps are involved: a) Preparation of nanometer-sized Fe3O4 particles by hydrothermal method; b) dispersing the nano-iron tetroxide particles in an ethanol solution, electrostatically spraying the nano-iron tetroxide particles on one side of the surface-treated porous carbon paper, and drying and sintering the nano-iron tetroxide particles to obtain an iron tetroxide / porous carbon paper composite material; c) immersing the ferroferric oxide / porous carbon paper composite material in an ammonium sulfide solution, washing and drying, to obtain a surface-modified ferroferric oxide / porous carbon paper composite material; d) Prepare polytetrafluoroethylene spray liquid, electrostatically spray it on the other side of the porous carbon paper, and obtain ferroferric oxide / super-hydrophobic carbon paper composite material after high-temperature sintering.
2. The method for preparing a hydrophobic modified material for removing odorous gases according to claim 1, characterized in that: In step a), the diameter of the ferrosoferric oxide particles is 80-200 nm.
3. The method for preparing a hydrophobic modified material for removing odorous gases according to claim 1, characterized in that: In step b), the surface treatment of the porous carbon paper includes: immersing the porous carbon paper in urea solution, deionized water, sodium hydroxide solution, anhydrous ethanol and deionized water in sequence for surface modification, and then ultrasonicating and drying to obtain the surface-treated porous carbon paper.
4. The method for preparing a hydrophobic modified material for removing odorous gases according to claim 3, characterized in that: In step b), the concentration of the urea solution is 4.0-6.0 mol / L, the concentration of the sodium hydroxide solution is 0.8-1.2 mol / L, and the soaking time is 15-20 min.
5. The method for preparing a hydrophobic modified material for removing odorous gases according to claim 1, characterized in that: In step b), each 1g of nano-iron tetroxide particles is dispersed in 8-15mL of anhydrous ethanol; the positive electrode voltage used for electrostatic spraying is 8.0-13.0 kV, the negative electrode voltage is 2.0-3.0 kV, the injection speed is 0.25-0.40 mm / min, and the syringe translation speed is 100-300 mm / min; the sintering temperature is 310-380°C, and the sintering time is 0.4-1.2 hours.
6. The method for preparing a hydrophobic modified material for removing odorous gases according to claim 1, characterized in that: In step c), the concentration of the ammonium sulfide solution is 0.2-0.4 mol / L, the reaction temperature is 45-55° C., and the reaction time is 10 min.
7. The method for preparing a hydrophobic modified material for removing odorous gases according to claim 1, characterized in that: In step d), the mass fraction of polytetrafluoroethylene in the polytetrafluoroethylene spray liquid is 52%-65%, the solvent is water, and ultrasonic dispersion and magnetic stirring are required before spraying; the positive electrode voltage used for electrostatic spraying is 19.0-23.0 kV, the negative electrode voltage is 1.5-3.0 kV, the injection speed is 0.25-0.40 mm / min, and the syringe translation speed is 100-300 mm / min; the sintering temperature is 310-360°C, and the sintering time is 0.3-0.8 hours.
8. The ferroferric oxide / super-hydrophobic carbon paper composite material prepared by the method according to any one of claims 1 to 7.